Detection of aniline oligomers on polyaniline-gold interface using resonance Raman scattering - Trchová, Miroslava; Morávková, Zuzana; Dybal, Jiří; Stejskal, Jaroslav (ACS applied materials & interfaces, 2014)
In situ deposited conducting polyaniline films prepared by the oxidation of aniline with ammonium peroxydisulfate in aqueous media of various acidities on gold and silicon supports were characterized by Raman spectroscopy. Enhanced Raman bands were found in the spectra of polyaniline films produced in the solutions of weak acids or in water on gold surface. These bands were weak for the films prepared in solutions of a strong acid on a gold support. The same bands are present in the Raman spectra of the reaction intermediates deposited during aniline oxidation in water or aqueous solutions of weak or strong acids on silicon removed from the reaction mixture at the beginning of the reaction. Such films are formed by aniline oligomers adsorbed on the surface. They were detected on the polyaniline-gold interface using resonance Raman scattering on the final films deposited on gold. The surface resonance Raman spectroscopy of the monolayer of oligomers found in the bulk polyaniline film makes this method advantageous in surface science, with many applications in electrochemistry, catalysis, and biophysical, polymer, or analytical chemistry.